2019
DOI: 10.1007/s00520-019-04687-3
|View full text |Cite
|
Sign up to set email alerts
|

Provider perceptions’ of a patient navigator for adolescents and young adults with cancer

Abstract: Purpose Healthcare providers (HCPs) and other staff at a comprehensive Cancer Center were interviewed on how to best implement a patient navigator position when working with adolescents and young adults (AYA) with cancer. Research objectives included assessing staff perceptions of (a) barriers to optimal care for AYA, (b) roles and responsibilities for a patient navigator, and (c) training needed for future patient navigators. Methods Semi-structured interviews were conducted with 17 staff members providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Patient navigators and supportive care professionals are well-poised to identify and address needs, values and communication styles of AYA cancer patients and survivors can serve as a conduit for identifying eligible patients for CCTs and relieve some responsibility from the primary medical team. One paramount role of the patient navigator is to serve as a first point of contact for the patient’s care team, with the ability to collaborate with other departments 30 . In this role, navigators can help bridge the knowledge gap of available AYA CCTs across pediatric and medical oncology departments, as is being studied by the AYA Program in Utah 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Patient navigators and supportive care professionals are well-poised to identify and address needs, values and communication styles of AYA cancer patients and survivors can serve as a conduit for identifying eligible patients for CCTs and relieve some responsibility from the primary medical team. One paramount role of the patient navigator is to serve as a first point of contact for the patient’s care team, with the ability to collaborate with other departments 30 . In this role, navigators can help bridge the knowledge gap of available AYA CCTs across pediatric and medical oncology departments, as is being studied by the AYA Program in Utah 31 .…”
Section: Discussionmentioning
confidence: 99%
“…13 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) supportive, for example in providing information and reassurance during treatment, was patient, and clear in communication. Furthermore, they indicated that the contact with the FN was pleasant because they were personal and showed empathy.…”
Section: Fns Guided Patients Through Fp Processmentioning
confidence: 99%
“…Support is provided by patient navigators (PNs), a role usually performed by nurses, social workers, or health educators who are trained for this role [ 17 , 18 ]. PNs fulfill the role of patient advocates for cancer patients; they provide additional information about medical procedures, refer patients for FP counseling, help patients schedule appointments, coordinate communication among the medical team, and navigate and support patients through the process [ 14 – 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%